2022
DOI: 10.1177/20552076221116776
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section telepathology service: Efficiency and benefits of an e-health policy in South Tyrol

Abstract: Objective/Background Telepathology has been widely adopted to allow intraoperative pathology examinations to be performed remotely and for obtaining second opinion teleconsultation. In the Italian northern region of South Tyrol, the widespread geographical distances and consequent cost for the health system of having a travelling pathologist cover intraoperative consultations in peripheral hospitals was a key driver for the implementation of a telepathology system. Methods In 2010, four Menarini D-Sight whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…On average, the scanning time per slide @40x magnification was <5 min, which was in concordance with high-end scanners used in other studies ( Table 1 ). 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Scanning at 20x can significantly reduce the scanning time (Average – 1:47 min/slide) using the same scanner as demonstrated in our previous study on FS. 8 Further, the image quality of these digitalised slides was reasonably good, despite few artefacts observed in these digital FS slides as expected due to inherent nature of FS glass slide preparation (more section thickness, folds and freezing artefacts – Fig 2 , Fig 7 ).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…On average, the scanning time per slide @40x magnification was <5 min, which was in concordance with high-end scanners used in other studies ( Table 1 ). 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Scanning at 20x can significantly reduce the scanning time (Average – 1:47 min/slide) using the same scanner as demonstrated in our previous study on FS. 8 Further, the image quality of these digitalised slides was reasonably good, despite few artefacts observed in these digital FS slides as expected due to inherent nature of FS glass slide preparation (more section thickness, folds and freezing artefacts – Fig 2 , Fig 7 ).…”
Section: Discussionmentioning
confidence: 61%
“…The median TAT of 27.27 min per case reported in the remote reporting arm in the current study was slightly longer than reported in the literature [range – 11–38 min/case (average 17.75 min) Table 1 ]. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 The longer time TAT in the current study was very significant, as it can challenge the clinical use of this system for FS interpretation as being a failure to meet the expected TAT of less than 20 min for FS reporting as per CAP recommendations. 29 …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Implementing digital pathology can be costly since it typically requires the purchase of scanners, computers, and infrastructure for image acquisition, storage, and delivery. In most cases, several factors could result in a return on investment [ 36 , 37 , 38 ]. Because both radiology and pathology are subspecialties dealing with image-intensive data, some authorities have advocated for joint radiology/pathology programs to manage the large images produced by scanners [ 39 , 40 ].…”
Section: Future Directionsmentioning
confidence: 99%